Selective ablation of immature blood vessels in established human tumors follows vascular endothelial growth factor withdrawal - Benjamin, Laura E.; Golijanin, Dragan; Itin, Ahuva; Pode, Dov; Keshet, Eli (The Journal of Clinical Investigation, 1999)
Features that distinguish tumor vasculatures from normal blood vessels are sought to enable the destruction of preformed tumor vessels. We show that blood vessels in both a xenografted tumor and primary human tumors contain a sizable fraction of immature blood vessels that have not yet recruited periendothelial cells. These immature vessels are selectively obliterated as a consequence of vascular endothelial growth factor (VEGF) withdrawal. In a xenografted glioma, the selective vulnerability of immature vessels to VEGF loss was demonstrated by downregulating VEGF transgene expression using a tetracycline-regulated expression system. In human prostate cancer, the constitutive production of VEGF by the glandular epithelium was suppressed as a consequence of androgen-ablation therapy. VEGF loss led, in turn, to selective apoptosis of endothelial cells in vessels devoid of periendothelial cells. These results suggest that the unique dependence on VEGF of blood vessels lacking periendothelial cells can be exploited to reduce an existing tumor vasculature.